Instituting interaction: normative transformations in human communicative practices - Elias, John Z.; Tylén, Kristian (Frontiers in Psychology, 2014)
Recent experiments in semiotics and linguistics demonstrate that groups tend to converge on a common set of signs or terms in response to presented problems. This process might be described as an implicit institutionalization of communicative practices, particularly when conventionalized to the point of overriding alternatives more functionally conducive to the current situation. However, the emergence of such convergence and conventionalization does not in itself constitute an institution, in the strict sense of a social organization partly created and governed by explicit rules. A further step towards institutions proper may occur when others are instructed about a task. That is, given task situations which select for successful practices, instructions about such situations make explicit what was tacit practice, instructions which can then be followed correctly or incorrectly. This transition gives rise to the normative distinction between conditions of success versus conditions of correctness, a distinction which will be explored and complicated in the course of this paper. Using these experiments as a basis, then, the emergence of institutions will be characterized in evolutionary and normative terms, beginning with our adaptive responses to the selective pressures of certain situational environments, and continuing with our capacity to then shape, constrain, and institute those environments to further refine and streamline our problem-solving activity.